2001
DOI: 10.1074/jbc.m100132200
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of Bacterial Protein Disulfide Isomerase (DsbC) and Its Modulator (DsbD) Markedly Enhances Periplasmic Production of Human Nerve Growth Factor in Escherichia coli

Abstract: Production of eukaryotic proteins with multiple disulfide bonds in the Escherichia coli periplasm often encounters difficulty in obtaining soluble products with native structure. Human nerve growth factor ␤ (NGF) contains three disulfide bonds between nonconsecutive cysteine residues and forms insoluble aggregates when expressed in E. coli. We now report that overexpression of Dsb proteins known to catalyze formation and isomerization of disulfide bonds can substantially enhance periplasmic production of NGF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…The e‹ciency of periplasmic production of NGF fused to an OmpT signal peptide was improved by coexpression of DsbCD or DsbABCD pro-teins. 12) These results revealed signiˆcant eŠects of Dsb proteins on recombinant protein production in the E. coli periplasm.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The e‹ciency of periplasmic production of NGF fused to an OmpT signal peptide was improved by coexpression of DsbCD or DsbABCD pro-teins. 12) These results revealed signiˆcant eŠects of Dsb proteins on recombinant protein production in the E. coli periplasm.…”
mentioning
confidence: 79%
“…15,16) In addition to PDI, overexpression of Dsb proteins has been shown to increase the yield of various eukaryotic proteins in bacteria. [8][9][10][11][12] Soluble BDNF production was estimated from the biological activity for neurite outgrowth of embryonic chick DRG neurons. Soluble BDNF fractions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, hNGF expression in E. coli cytoplasm has led to aggregated proteins (10)(11)(12)(13)(14)(15)(16)21). Thus, the soluble expression of hNGF in E. coli has been considered a challenging task.…”
mentioning
confidence: 99%
“…In reported studies bacterial expression of human NGF demonstrated the feasibility of overproduction but also limitations in the use of E. coli as an expression host for a protein with three intra-chain disulfide bonds (10)(11)(12)(13)(14)(15)(16). Isolation and purification of hNGF from inclusion bodies require solubilization followed by refolding.…”
mentioning
confidence: 99%
“…In E. coli, disulfide bond isomerization is the limiting step in the oxidative folding of many heterologous proteins that contain multiple cysteines. Overexpression of DsbC has been shown to enhance the yield of proteins such as human nerve growth factor, human tissue plasminogen activator (tPA) 2 and immunoglobulins (17)(18)(19). DsbC is topologically analogous to the eukaryotic proteindisulfide isomerase (PDI).…”
mentioning
confidence: 99%